66 Regional variations in aed deployment, accessibility and early defibrillation: a nationwide study. (16th April 2018) - Kjølbye, JS; Karlsson, L; Lippert, FK; Hansen, CM; Andelius, L; Møller, S; Wodschow, K; Ersbøll, AK; Torp-Pedersen, C; Gislason, GH; Folke, F
Abstract : Aim: Current resuscitation guidelines recommend early defibrillation by publicly accessible automated external defibrillators (AEDs). However, little is known on regional variations in AED deployment, 24/7 accessibility and bystander defibrillation on a nationwide level. Method: We identified all publicly available AEDs registered in the Danish AED network (2007–2016). AED density, type of location, 24/7 accessibility and bystander defibrillation were examined according to regional differences in Denmark. Results: Of 17, 106 AEDs registered nationwide (=297.7 AEDs/100, 000 inhabitants), the largest quantity and density of AEDs were in The Capital Region (n=5, 120, 29.9%), 110.8 AEDs/100, 000 inhabitants/1000 km2, followed by Southern Denmark (n=4, 082, 23.9%), 27.4 AEDs/100, 000 inhabitants/1000 km2, Central Jutland (n=3, 644, 21.3%), 21.5 AEDs/100, 000 inhabitants/1000 km2, Zealand (n=2, 269, 13.3%), 37.8 AEDs/100, 000 inhabitants/1000 km2 and Northern Jutland (n=1, 991, 11.6%), 43.0 AEDs/100, 000 inhabitants/1000 km2. Northern Jutland had the highest proportion of 24/7 AED accessibility (50.2%), followed by Southern Denmark (47.5%), Zealand (44.5%), Central Jutland (41.0%) and The Capital Region (29.1%). The corresponding public defibrillation rates were 12.5%, 23.5%, 9.7%, 13.5% and 11.8%, respectively. 'Companies/offices' were the most frequent location for AED placement in all five regions, however, with a low 24/7 accessibility ranging from 11.4% to 31.3%. Conclusion: In Denmark, we found a marked difference in regional AED density ranging from 21.5 to 110.8 AEDs/100, 000 inhabitants/1000 km2, as well as 24/7 accessibility ranging from 29.1% to 50.2%. The most frequent location of AED placement for all regions was 'Companies/offices', which generally had low 24/7 accessibility. Finally, public OHCA defibrillation rates ranged from 9.7% to 23.5%. Conflict of interest: None Funding: The Danish AED Network and The Danish Cardiac Arrest Registry are funded by The private Foundation TrygFonden with no commercial interest in the field of cardiac arrest.